Attaching reflected experience on TOEFL learning through scaffolding teaching - Rochman, Diah Gusrayani (Universitas Islam Sultan Agung, 2024)
This research aims to explore the impact of positive psychology, experiential learning (EL), and scaffolding on classroom engagement and motivation, focusing on enhancing teaching and learning effectiveness. It was conducted with 44 students and two instructors who implemented scaffolding guidance in shared experience sessions. The research design involved pre and post-tests to assess changes in students' classroom engagement and motivation levels, resulting from the application of scaffolding teaching and experiential learning (EL) methods. Analysis of pre and post-test results suggests that scaffolding teaching and EL methodologies significantly impact students' classroom engagement and motivation. The study found these methods to enhance the quality of teaching and learning by emphasizing the development of abilities and experiences. This study underscores the value of integrating scaffolding and EL into educational practices to bolster students' engagement and motivation in the classroom setting. The exploration of various tips and strategies drawn from shared experiences revealed their effectiveness in improving test scores and overall learning outcomes. In conclusion, this study advocates for the broader application of these methodologies to foster improved educational achievements and learner experiences.